MEMBINCANG PENDEKATAN KONTEKSTUALIS ABDULLAH SAEED DALAM MEMAHAMI AL-QUR’AN - M. Solahudin (Institut Agama Islam Negeri (IAIN) Keiri, 2018)
Qur’anic studies never ends. It is done by both intellectual moslems and orientalists (non moslem). Abdullah Saeed, an intellectual moslem who lives in non moslem area (Australia), is one of those who studies Qur’an deeply. To understand and interpret Qur’an contextually, he offers an approach called contextualist approach. Then, Saeed also makes hierarchy of values taken from Qur’anic verses. This is known that not all verses must be conformed to place and time, but some should be understood and interpreted universally. While others depend on place and time (particularly). The steps of interpreting, called model of interpretation by Saeed, with contextualist approach encounter with the world of the text, critical analysis, meaning for the first recipients, and meaning for the present. an example of Saeed’s interpretation of the verses about usury connected to interest is given in the last of this article.